Satellite cell proliferation in response to a chronic laboratory-controlled uphill vs. downhill interval training intervention - Eksteen, Gabriel Johannes (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2006.